Aplikasi Bimbingan Konseling Berbasis Web Di Smk Negeri 16 Samarinda - Raisman Adhitya; Fahrullah; Dedy Mirwansyah (LPPM Universitas Nias Raya, 2022)
In conducting Counseling Guidance, especially at SMK Negeri 16 Samarinda, currently experiencing problems, including finding it difficult to re-search the counseling history and cellphone memory of BK teachers which became full quickly because counseling chats that must be stored until recording in the counseling data book in schools. In this study, a counseling guidance application was developed that can help the counseling guidance process and the search for past counseling history. This application was created using php programming language and database server using MYSQL and the method used is prototype as the basis for writing specifications for the system and is also the basis for the development of software. With this application, it can help BK teachers in the counseling guidance process and simplify the process of re-finding past counseling histories.